2017
DOI: 10.5213/inj.1732774.387
|View full text |Cite
|
Sign up to set email alerts
|

Near-Normalized Gene Expression Profiles in Bladder With Detrusor Overactivity in Rats With Bladder Outlet Obstruction After Deobstruction

Abstract: PurposeThe pathophysiological role of detrusor overactivity (DO) in the bladder, which is commonly observed in various bladder diseases, is not well understood. DO appears in bladder outlet obstruction (BOO), and may continue even after subsequent deobstruction. DO therefore provides an excellent opportunity to observe molecular biological changes.MethodsIn this study, to understand the molecular effects of persistent DO after BOO induction and deobstruction, we performed awake cystometry on female Sprague-Daw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
(25 reference statements)
1
5
0
Order By: Relevance
“…The results showed that many of the genes were categorized into the molecular functions category, including cytokines and cytokine receptors (Fig. 2B), consistent with the results of previous studies using BOO model rats 4,16 .…”
Section: Total Gene Expression Pro Les In the Mh And Sh Groupssupporting
confidence: 90%
See 1 more Smart Citation
“…The results showed that many of the genes were categorized into the molecular functions category, including cytokines and cytokine receptors (Fig. 2B), consistent with the results of previous studies using BOO model rats 4,16 .…”
Section: Total Gene Expression Pro Les In the Mh And Sh Groupssupporting
confidence: 90%
“…In the decompensation stage, loss of smooth muscle, deposition of extracellular matrix, and degradation of neurons occur under the sustained stress caused by obstruction. In each stage of the bladder remodeling, several signaling pathways are modulated in the various compartments of the bladder in animal models of BOO and human patients with BOO 3,4 . Alterations in gene expression at the initiation of bladder remodeling play important roles as triggers of disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several efforts in the urology field to elucidate the genes related to the IRI pathway [21]. Toll-like receptors, sphingosine-1-phosphate receptors, and hypoxiainducible factors have been reported to worsen tubular epithelial cell function, eventually causing acute renal damage, delayed graft function, and ultimately acute-on-chronic rejection [22].…”
Section: Corm-3 Ameliorates Ischemia-reperfusion Injurymentioning
confidence: 99%
“…Already research studies revealed that C. obtusa has anti-inflammatory effect (Kim et al, 2015; Rufino et al, 2014). Inflammation is on action for a variety of reason (Lee et al, 2017; Park et al, 2018; Song et al, 2017). If inflammation action in the skin, it can be various reactions such as increase of blood flow blood flow increase, cell metabolism enhancement, vasodilation to defend and recover (Ferrero-Miliani et al, 2007).…”
Section: Introductionmentioning
confidence: 99%